TGFβ1 rapidly activates Src through a non-canonical redox signaling mechanism - Zhang, Hongqiao (Arch Biochem Biophys, 2015)
Transforming growth factor-β1 (TGF-β) is involved in multiple cellular processes through Src activation. In the canonical pathway, Src activation is initiated by pTyr530 dephosphorylation followed by a conformational change allowing Tyr419 auto-phosphorylation. A non-canonical pathway in which oxidation of cysteine allows bypassing of pTyr530 dephosphorylation has been reported. Here, we examined how TGF-β activates Src in H358 cells, a small cell lung carcinoma cell line. TGF-β increased Src Tyr419 phosphorylation, but surprisingly, Tyr530 phosphorylation was increased rather than decreased. Vanadate, a protein tyrosine phosphatase inhibitor, stimulated Src activation itself, but rather than inhibiting Src activation by TGF-β, activation by vanadate was additive with TGF-β showing that pTyr530 dephosphorylation was not required. Thus, the involvement of the non-canonical oxidative activation was suspected. TGF-β increased extracellular H(2)O(2) transiently while GSH-ester and catalase abrogated Src activation by TGF-β. Apocynin, a NADPH oxidase inhibitor, inhibited TGF-β-stimulated H(2)O(2) production. Furthermore, mutation of cysteines to alanine, 248C/A, 277C/A, or 501C/A abrogated, while 490C/A significantly reduced, TGF-β-mediated Src activation. Taken together, the results indicate that TGF-β-mediated Src activation operates largely through a redox dependent mechanism, resulting from enhanced H(2)O(2) production through an NADPH oxidase and that cysteines 248, 277, 490, and 501 are critical for this activation.